Dental management prior to radiation therapy in patients with head and neck cancer - Bonar Alvarez, Paula; Perez-Sayans, Mario; Oliveira Alves, Monica Ghislaine [UNESP]; Gallas Torreira, Mercedes; Padin Iruegas, Maria Elena; Blanco Carrion, Andres; Garcia-Garcia, Abel (Wolters Kluwer Medknow Publications, 2018)
INTRODUCTION: Patients diagnosed with head and neck tumors, are treated by surgery, radiation therapy (RT), chemotherapy (CT) or a combination thereof. The goal is to describe the management protocol for patients subjected to radiation therapy (RT) and to study their long-term oral health status. MATERIALS AND METHODS: A retrospective study was performed in a sample of 50 patients. We analyzed the oral health status and all the variables included applying the adapted protocol of pre-RT. RESULTS: Prior to RT, 84% of patients required scaling and 32% conservative treatment. Around 74% of patients required at least one exodontia. The mean of exodontias for patients presenting Grade 3 of oral hygiene was 6.50 per person (p<0.0001). The pre-RT study of possible candida infection showed that 78% of patients were negative for this infection. The mean resting saliva production was 39.10 (SD: 23.30; range: 13-145), with a stimulated value of 64.78 (SD: 33.92; range: 16-200). CONCLUSIONS: All patients should be protocoled to ensure that they present optimal oral conditions prior to initiating RT treatment.
Keywords: Head and neck tumors; oral health status; oral hygiene; radiotherapy; saliva